2018
DOI: 10.1186/s13046-018-0957-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-296-5p suppresses EMT of hepatocellular carcinoma via attenuating NRG1/ERBB2/ERBB3 signaling

Abstract: BackgroundAccumulation of evidence indicates that miRNAs have crucial roles in the regulation of EMT-associated properties, such as proliferation, migration and invasion. However, the underlying molecular mechanisms are not entirely illustrated. Here, we investigated the role of miR-296-5p in hepatocellular carcinoma (HCC) progression.MethodsIn vitro cell morphology, proliferation, migration and invasion were compared between HCC cell lines with up- or down-regulation of miR-296-5p. Immunofluorescence and West… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 42 publications
4
63
1
Order By: Relevance
“…10,11 Speaking of cancer metastasis, epithelial-mesenchymal transition (EMT) is a process closely related to metastasis through which terminal differentiated epithelial cells transform to migratory mesenchymal cells during embryo development. 12 During past years, the inhibition of EMT progression by miRNAs has been identified in numerous cancers, such as in hepatocellular cancer, 13 colorectal cancer, 14 and ccRCC. 15 Furthermore, numerous miR-NAs have been identified in ccRCC to exhibit oncogenic or tumor-suppressive functions.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Speaking of cancer metastasis, epithelial-mesenchymal transition (EMT) is a process closely related to metastasis through which terminal differentiated epithelial cells transform to migratory mesenchymal cells during embryo development. 12 During past years, the inhibition of EMT progression by miRNAs has been identified in numerous cancers, such as in hepatocellular cancer, 13 colorectal cancer, 14 and ccRCC. 15 Furthermore, numerous miR-NAs have been identified in ccRCC to exhibit oncogenic or tumor-suppressive functions.…”
Section: Introductionmentioning
confidence: 99%
“…By the means of dual luciferase reporter assay and RIP, miR‐296‐5p was validated as the direct binding target for hsa_circ_001895. miR‐296‐5p is a tumor suppressor in various tumors . The present study indicated that hsa_circ_001895 knockdown inhibited ccRCC progression but induced cell apoptosis through sponging miR‐296‐5p.…”
Section: Discussionmentioning
confidence: 52%
“…High expression of ERBB3 in certain human cancers led early on to the suggestion that it could be a therapeutic target . ERBB3 was reported to have an oncogenic role in HCC . The most fully studied target of ERBB3 is the p85 regulatory subunit of PI3K (PI3KR).…”
Section: Discussionmentioning
confidence: 99%